2019
DOI: 10.7554/elife.43775
|View full text |Cite
|
Sign up to set email alerts
|

A bidirectional network for appetite control in larval zebrafish

Abstract: Medial and lateral hypothalamic loci are known to suppress and enhance appetite, respectively, but the dynamics and functional significance of their interaction have yet to be explored. Here we report that, in larval zebrafish, primarily serotonergic neurons of the ventromedial caudal hypothalamus (cH) become increasingly active during food deprivation, whereas activity in the lateral hypothalamus (LH) is reduced. Exposure to food sensory and consummatory cues reverses the activity patterns of these two nuclei… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
58
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 66 publications
(62 citation statements)
references
References 72 publications
4
58
0
Order By: Relevance
“…The OXT circuit modulates nocifensive behavior via brainstem premotor neurons 6 . Since it projects extensively into other parts of the hypothalamus, as well as the pituitary gland, these downstream regions may be involved in mediating its effects appetite 25 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The OXT circuit modulates nocifensive behavior via brainstem premotor neurons 6 . Since it projects extensively into other parts of the hypothalamus, as well as the pituitary gland, these downstream regions may be involved in mediating its effects appetite 25 .…”
Section: Resultsmentioning
confidence: 99%
“…In mammals, social isolation is associated not only with increases in aversive behavior, but also with a reduction in positive-valence behaviors such as feeding 22 . To determine if this is also the case in larval zebrafish, we first made use of an established and quantitative food intake assay that measures gut fluorescence intensity caused by the ingestion of fluorescently-labeled paramecia 2325 (Fig. 4a).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The authors showed that food‐deprived larvae had active neurons at the caudal hypothalamus (CH), but inactive ones in the lateral hypothalamus (LH). This was reversed during meals when neuronal activity switches “off” at CH and “on” at LH (Wee et al, 2019). The transgenic zebrafish lines used in that study (Wee et al, 2019) do not exist in Astyanax CF.…”
Section: Subterranean Life With Scarce Foodmentioning
confidence: 99%